REGROWTH AND YIELD Asystasia gangetica (L.) subsp. Micrantha ON VARIOUS DECOMPOSITION TIME AND DOSE OF CHICKEN MANURE FERTILIZER - K. J., Wiranatha; Duarsa, M. A. P.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika, 2023)
This study aimed to determine the effect between decomposition time and dosages of chicken manure on regrowth and yield Asystasia gangetica (L.) subsp. Micrantha. The research was conducted at the Greenhouse, Sesetan Research Station, Faculty of Animal Husbandry, Udayana University. The study lasted for 8 weeks, using a completely randomized design (CDR) with factorial pattern. The first factor was the decomposition time of 4 weeks (W4), 2 weeks (W2), without decomposition (W0). The second factor was levels of chicken manure: 0 ton ha -1 (D0), 10 tons ha -1 (D20), 20 tons ha -1 (D20), and 30 tons ha -1 (D30). There were 12 treatment combination each treatment was repeated four times, so there were 48 experimental units. Variables measured in this experiment were growth, yield, and plant growth characteristic variables. The result showed that there was an interaction between decomposition time and dosage of chicken manure on all variable, except on the variables of the number of branches, dry weight of roots, and dry weight of stem and leaf. The W0 showed better result than W4 and W2 treanments. The best dosage of chicken manure was observed D10 treatment. Based on above results, it is concluded that Asystasia gangetica (L.) subsp. Micrantha response the best during decomposition 0 week at 10 tons ha -1 chicken manure. Key words: Asystasia gangetica, chicken manure, decomposition, regrowth, yield